Power and persuasion : fiestas and social control in rural Mexico - Brandes, Stanley H. (University of Pennsylvania Press, 1988)
Demonstrates how the annual fiesta cycle reflects political dependency of local communities on the nation-state, helps maintain formal authority, and perpetuates behavioral norms and social values.